Histological Features of the Duodenum of Mice (Mus musculus) Treated with Liquid Probiotic Isolates of Bacillus coagulans, Bacillus subtilis, and Saccharomyces cerevisiae - Devi Sri Rohmani; Mohammad Anam Al Arif; Sri Agus Sudjarwo; Mohammad Sukmanadi; Eka Pramyrtha Hestianah; Widya Paramita Lokapirnasari (Universitas Airlangga, 2024)
This study aims to determine the histological description of the height and width of the duodenal villi of mice (Mus musculus) treated with liquid probiotic isolates of Bacillus coagulans, Bacillus subtilis, and Saccharomyces cerevisiae. Histological examination of the duodenum of mice was carried out by making histological preparations from the height and width of the duodenal villi which were observed under a microscope with 100x magnification. Statistical analysis in this study used One-Way ANOVA and Duncan's test. The results showed that the control group and the treatment group had significantly different height and width of the duodenal villi (p<0.05). The conclusion of this study is that the administration of isolates Bacillus coagulans, Bacillus subtilis, and Saccharomyces cerevisiae can increase the height and width of the duodenal villi of mice and the P2 group with a dose of 0.27 mL/kg BW has the greatest average value for the height and width of the duodenal villi with an average height of 360.80 Î¼m and an average width of 152.30 Î¼m.